2008
DOI: 10.1159/000114097
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation Normalized Hydrogen Peroxide Production of Neutrophils within the First Day

Abstract: Background: Hemodialysis patients are in a state of oxidant stress. In renal transplantation reactive oxygen species (ROS) are considered to be important factors of ischemia-reperfusion injury. Neutrophils produce ROS as part of the host defense against invading bacteria. This study was designed to investigate whether neutrophil function in hemodialysis patients is immediately affected by renal transplantation. Methods: We evaluated the neutrophil respiratory burst and phagocytic activity in renal transplant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In addition, activated neutrophils undergo rapid apoptosis [8] , [44] and NETosis [45] , [46] , releasing DNA, myeloperoxidase and proteases creating a highly reactive and oxidative environment capable of inducing lipid peroxidation and generating reactive lipid species such as 4-HNE. The uncontrolled generation of reactive metabolites in chronic inflammatory diseases has been shown to induce cellular and organelle dysfunction in a variety of cell types [47] , [48] . In vivo and in vitro experimental models support this hypothesis and suggest that increased oxidative stress has profound effects on leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activated neutrophils undergo rapid apoptosis [8] , [44] and NETosis [45] , [46] , releasing DNA, myeloperoxidase and proteases creating a highly reactive and oxidative environment capable of inducing lipid peroxidation and generating reactive lipid species such as 4-HNE. The uncontrolled generation of reactive metabolites in chronic inflammatory diseases has been shown to induce cellular and organelle dysfunction in a variety of cell types [47] , [48] . In vivo and in vitro experimental models support this hypothesis and suggest that increased oxidative stress has profound effects on leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas MPO level rose one h after reperfusion, and was significantly increased 24 h after reperfusion in both studied groups. We concluded that this elevation resulting from Kupffer cell activation and generation of ROS, which is characterized by massive neutrophil graft infiltration and further production of the inflammatory mediators (8, 21). In this context we found CRP, which is produced only by hepatocytes (22), and PCT levels significantly increased from 1 to 24 h after reperfusion (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…During liver transplantation, the reperfusion phase is associated with Kupffer cell activation, release of pro‐inflammatory cytokines such as TNF‐α, interleukin 1, activated complement factors, platelet‐activating factor, and generation of ROS (8). These cytokines, together with the increased expression of adhesion molecules by sinusoidal endothelial cells, promote liver neutrophil infiltration, thus contributing to the progression of parenchymal injury (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as we described recently [ 18 ], respiratory burst activity was determined with the content of rhodamine (FL 1) in the phagocytic cells, expressed as mean fluorescence intensity of the FL 1 histogram.…”
Section: Methodsmentioning
confidence: 99%